2001
DOI: 10.3310/hta5140
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and systematic review of the clinical effectiveness and cost-effectiveness of debriding agents in treating surgical wounds healing by secondary intention

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 58 publications
0
35
0
5
Order By: Relevance
“…The wound may require additional attention after the debridement performed during the initial assessment (table 4). The goal is to physically excise dead and unhealthy tissue, thereby enabling wound healing and removing a reservoir of potential pathogens [82,[192][193][194]. Any experienced clinician may perform limited debridement.…”
Section: Treatment Of Infectionmentioning
confidence: 99%
“…The wound may require additional attention after the debridement performed during the initial assessment (table 4). The goal is to physically excise dead and unhealthy tissue, thereby enabling wound healing and removing a reservoir of potential pathogens [82,[192][193][194]. Any experienced clinician may perform limited debridement.…”
Section: Treatment Of Infectionmentioning
confidence: 99%
“…Overall, modern occlusive dressings were favored over gauze dressings for healing. Findings from individual trials in the review 79 produced no clear evidence of differences in rates of healing among polyurethane foam, silicone foam, and alginate dressings. Several authors 78,81,84 have investigated the effectiveness of autolytic, wet-to-dry, and enzymatic debridement among various chronic wounds.…”
Section: 70mentioning
confidence: 93%
“…Autolytic debridement is the use of the body's mechanisms to promote proteolytic digestion of necrotic tissue in a moist environment created by the application of occlusive dressings such as alginates, films, foams, hydrogels, and hydrocolloids. 76,79,83,85 The moist environment allows endogenous collagenase enzymes within the wound to liquefy necrotic tissue, which can then be more easily digested by macrophages. 51,55,57,58,75,77,80,82 The body selectively digests only nonviable tissue and the moist environment allows for painless debridement.…”
Section: 70mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of dressings and topical agents for contaminated and infected wounds is not always based on a firm rationale. 27 In the trial of Münter, patients treated with silver-containing foam experienced less pain, showed a quicker reduction of odour, and required less frequent dressing changes due to leakage. These secondary advantages of silver can be used in balancing the pros and cons for the use of silver.…”
Section: Resultsmentioning
confidence: 99%